An efficient field programmable gate arrays based real‐time implementation of smooth variable structure filter to estimate the state of charge of Li‐ion battery in electric vehicle application - Sabeur Jemmali; Mahmoud Hamouda; Bilal Manaï (IET Electrical Systems in Transportation)
Abstract The computational efficiency is a challenging task in the real‐time implementation of battery State of Charge (SoC) estimation algorithms in Electric Vehicle (EV) application. This study proposes for the first time a pure hardware architecture of a Smooth Variable Structure Filter (SVSF) to estimate the SoC of a lithium‐ion battery in an EV. The proposed embedded architecture is implemented on a Xilinx Zynq‐7000 field programmable gate arrays board without using any soft‐core, and validated with real‐time tests carried out on a 20 Ah NMC battery with nominal voltage about 3.65 V. The whole embedded architecture of the SVSF needs a reduced execution time in the range of 921 ns, and it consumes only 466 mW. The average estimation errors of the SoC and battery voltage at different temperatures are kept within 4.95% and 2.35% respectively. The successful convergence of the algorithm and the accurate results obtained in different circumstances, prove the practicability and computational efficiency of the proposed hardware architecture.